1991
DOI: 10.1111/j.1365-2125.1991.tb03864.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clonidine and yohimbine on the pupillary light reflex and carbachol‐evoked sweating in healthy volunteers.

Abstract: The effects of single doses of clonidine hydrochloride (200 ,ug), yohimbine hydrochloride (22 mg), a combination of the two treatments, and placebo, on some autonomic functions were studied in healthy volunteers using a double-blind crossover design. Clonidine prolonged the recovery time of the light reflex, lowered systolic blood pressure and reduced subjectively rated alertness; these effects were reversed by yohimbine. Responsiveness of sweat glands to carbachol was not affected by the treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
31
3
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 8 publications
12
31
3
3
Order By: Relevance
“…In the present experiment, a single dose of 0.2 mg clonidine reduced both the subjective and the objective level of alertness in healthy volunteers (see Table 1), in agreement with previous reports (Morley et al, 1991;Kumari et al, 1996;Abduljawad et al, 1997Abduljawad et al, , 2001Phillips et al, 2000d;Hou et al, 2005. Alertness was robustly increased by a single dose of 400 mg modafinil, in contrast to previous reports using a 200-mg single dose where either a small effect (Hou et al, 2005(Hou et al, , 2007 or no effect of modafinil in healthy non-sleep-deprived volunteers was observed.…”
Section: Discussioncontrasting
confidence: 56%
“…In the present experiment, a single dose of 0.2 mg clonidine reduced both the subjective and the objective level of alertness in healthy volunteers (see Table 1), in agreement with previous reports (Morley et al, 1991;Kumari et al, 1996;Abduljawad et al, 1997Abduljawad et al, , 2001Phillips et al, 2000d;Hou et al, 2005. Alertness was robustly increased by a single dose of 400 mg modafinil, in contrast to previous reports using a 200-mg single dose where either a small effect (Hou et al, 2005(Hou et al, , 2007 or no effect of modafinil in healthy non-sleep-deprived volunteers was observed.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, the slopes and intercepts of the fitted regression lines did not differ significantly in the presence of the antidepressants from those observed in the presence of placebo, indicating that the observed reduction in recovery time ( Figure 1, Table 2) is likely to be the reflection of the reduction in reflex response amplitude. It is possible that the reduction in amplitude in the presence of the antidepressants militated against the detection of any effect on the sympathetic input, since previous studies have suggested that a sympathetic contribution to the recovery phase of the light reflex response becomes apparent only at larger response sizes [5,6]. In theory, the range of response amplitudes in the presence of the antidepressants could have been extended to the same level as observed in the presence of placebo by the application of more intense light stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The computer could be programmed to pass current pulses of predetermined intensity and duration through the diodes and also to determine the time intervals between the applications of successive stimuli. The following twelve light intensities were used: 5.3 x 10-5, 1.5 x 104, 5.0 x 10-4, 1.7 x 10-3, 5.3 x 10-, 1.5 x 10-2, 4.6 x 10-2, 0.13, 0.36, 0.86, 1.86 and 3.5 mW cm-2 (measured 1 cm from the light source). The stimulus duration was 500 ms, and the interval between successive stimuli was 20 s.…”
Section: Apparatusmentioning
confidence: 99%
See 2 more Smart Citations